The relationship of physical balance to the utilization of pelleted and nonpelleted rations for lambs - Menzies, C.; Bell, T.D.; Richardson, D.; Cox, R.F.; Striegel, W.D. (Kansas Agricultural Experiment Station, 2011)
Physical balance of lamb-fattening rations has been studied in this project for several years. This is the fourth year that this project has been set up to study the effect of pelleting rations of varying proportions of roughages and concentrates upon feed-lot performance and feed efficiency compared with similar unpelleted rations. For the past two years both dehydrated and field-cured alfalfa hay have been used as roughages.
Keywords: Sheep; Pelleted rations; Nonpelleted rations; Performance; Feed efficiency